Risky Relationships and Teen Dating Violence Among At-Risk Adolescents, Charlottesville, Virginia, 2010-2012 - Reppucci, N. Dickon ([Verlag nicht ermittelbar], 2023)
Teen dating violence is linked to numerous longstanding consequences, such as delinquency, risky sexual behavior, and adult partner violence. The purpose of Project D.A.T.E. (Demand Appreciation, Trust, and Equality) was to address gaps in current research by focusing on romantic relationship experiences among at-risk adolescents living in and around Charlottesville, Virginia. The research team investigated risk and protective factors related to teen dating violence and positive relationship outcomes within a single relationship and across multiple relationships. The team also explored how early abusive relationships impact trajectories into later abusive relationships, and how age gaps between romantic partners might contribute to victimization and other negative outcomes. The specific research questions for this longitudinal survey-based study were as follows: What risk and protective factors are related to teen dating violence and positive relationship outcomes within a single target relationship? What factors are associated with abuse across multiple relationships, and do early abusive relationships increase the likelihood youth will continue to experience abuse in future relationships? How are relationship-level characteristics associated with relationship abuse? Are adolescents at greater risk for victimization and negative reproductive health outcomes if they date older partners, and if so, why? Participants included 223 adolescents (58% female, 61% African-American) who (1) were between 13 and 18 years old, (2) answered yes to "Have you ever 'dated someone' or been in a romantic relationship that lasted at least 1 month?", and (3) received community-based services (e.g., foster care, alternative schooling) or low-income services (e.g., free or reduced lunch, low-income housing). Participants completed two waves of two-hour, in-person, self-report interviews that took place about a year apart. In each interview, participants answered questions about abuse, intimacy, and health within up to three romantic relationships (thus, up to six relationships across two waves of data collection), in addition to socio-demographics, family, and schooling measures.